Inovasi Layanan PT Mitra Tour Dan Travel Dalam Meningkatkan Kualitas Pelayanan Sebagai Upaya Eksistensi Di Era Persaingan Global - Ali Muhajir (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2020)
This study aims to describe the innovations that have been made by PT. Mitra Tour and Travel Gresik and describe the service quality of PT. Tour and Travel Partners after making innovation as an effort to exist in the era of global competition. This type of research used by researchers is descriptive qualitative. Data collection techniques in this study were interviews, documentation and observation. Data analysis techniques consist of data reduction, data presentation and conclusion drawing. The results showed that the service innovation that had been developed by PT. Tour and Travel Partners are PLN payments, PDAM payments, BPJS payments, internet payments, top up credit, Multi finance, tax and vehicle registration, delivery of packages and documents, money transfers, and OVO, Brizzi, Link Aja, Dana iso balances. For service quality PT. Mitra Tour and Travel seen from the tangible dimensions, reliability, responsiveness, assurance and empathy in general are very good.